A sociedade do avatar: do eu heteronímico ao cibercultural - Cavalheiro, Gustavo Augusto Tavares (2010)
Based on the analisys of the historical and cultural relationship that, in the literary heteronomy, is developed by the current propensity to the digital alterity, this study points out the similarities, differences and similitudes between the civil person, the cybercultural spectrum and images of "self-other". The presentation of the subject and the problem focus on questioning the construction and acceptance of the real/true in his overlaps of forged identification, which can be widely discussed in the pre-cybercultural period. Bringing to the comunication, the elements and concepts of being (far/close) yourself as much as the mediatic structures builds and/or translates the civil society as an imagery (re/a)presentation of yourself; is it studied the expansion of yourself in the digital space in a digital nets new time-untimed, from the image to the formation of an "other" (or personaskilled) and its seduction built under the logic of appearance design construction /management/power of an Avatar